Compensation of Dosage-Sensitive Genes on the Chicken Z Chromosome. (4th April 2016) - Zimmer, Fabian; Harrison, Peter W.; Dessimoz, Christophe; Mank, Judith E.
Abstract : In many diploid species, sex determination is linked to a pair of sex chromosomes that evolved from a pair of autosomes. In these organisms, the degeneration of the sex-limited Y or W chromosome causes a reduction in gene dose in the heterogametic sex for X- or Z-linked genes. Variations in gene dose are detrimental for large chromosomal regions when they span dosage-sensitive genes, and many organisms were thought to evolve complete mechanisms of dosage compensation to mitigate this. However, the recent realization that a wide variety of organisms lack complete mechanisms of sex chromosome dosage compensation has presented a perplexing question: How do organisms with incomplete dosage compensation avoid deleterious effects of gene dose differences between the sexes? Here we use expression data from the chicken ( Gallus gallus ) to show that ohnologs, duplicated genes known to be dosage-sensitive, are preferentially dosage-compensated on the chicken Z chromosome. Our results indicate that even in the absence of a complete and chromosome wide dosage compensation mechanism, dosage-sensitive genes are effectively dosage compensated on the Z chromosome.